2019
DOI: 10.1039/c9nj03233a
|View full text |Cite
|
Sign up to set email alerts
|

Mixed solvent exfoliated transition metal oxides nanosheets based flexible solid state supercapacitor devices endowed with high energy density

Abstract: Mixed solvent exfoliated transition metal oxide nanosheet/SWCNT composite based flexible supercapacitors demonstrate large specific capacitance and high energy density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 97 publications
0
21
0
Order By: Relevance
“…The surface area of Mn, Zn co‐doped NiCo 2 O 4 is three times higher than the pure NiCo 2 O 4 . The high surface area and mesoporous nature of the Mn, Zn co‐doped NiCo 2 O 4 nanocomposite enhances the electrochemical activity by shortening the ion pathways, enhancing the contact area, enriches the redox active sites, improving the electrolyte penetration through the mesopores, and facilitates the charge transfer kinetics compared with pure NiCo 2 O 4 [27] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface area of Mn, Zn co‐doped NiCo 2 O 4 is three times higher than the pure NiCo 2 O 4 . The high surface area and mesoporous nature of the Mn, Zn co‐doped NiCo 2 O 4 nanocomposite enhances the electrochemical activity by shortening the ion pathways, enhancing the contact area, enriches the redox active sites, improving the electrolyte penetration through the mesopores, and facilitates the charge transfer kinetics compared with pure NiCo 2 O 4 [27] …”
Section: Resultsmentioning
confidence: 99%
“…[26] Furthermore, the Mn, Zn ical activity by shortening the ion pathways, enhancing the contact area, enriches the redox active sites, improving the electrolyte penetration through the mesopores, and facilitates the charge transfer kinetics compared with pure NiCo 2 O 4 . [27]…”
Section: Brunauer -Emmett -Teller Analysismentioning
confidence: 99%
“…Z. et al, 2015;Peng et al, 2017;Zavabeti et al, 2017;Tao et al, 2019). It is reported that MoO 3 , MnO 2 , and RuO 2 nanosheets, etc., can be made at a large scale by ultrasonic exfoliation in ethanol/water and can be applied to solid-state symmetrical supercapacitors (Dutta et al, 2019). A liquid-phase exfoliation method with the aid of lithium (Li) intercalation and deintercalation was developed for the preparation of quasi-layered VO 2 ultrathin nanosheet (Liu et al, 2012).…”
Section: Two-dimensional Transition Metal Oxides/hydroxidesmentioning
confidence: 99%
“…Besides that the NiCo2O4 nanosheet produces a small cell voltage of 1.59 V to drive a current density of 10 mA cm -2 compared to for Co3O4 catalyst [21][22][23] . Therefore, it is crucial to engineer different types of metal-ligand coordination to create abundant active sites for the electrocatalysis based on the lattice structure [24][25][26][27][28]…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%